The territorial Conservative Party : Devolution and party change in Scotland and Wales - Convery, Alan (Book collections on Project MUSE., 2016)
How did the territorial Conservative Party adapt to devolution? This detailed analysis of the Scottish and Welsh Conservative Parties explains how they moved from campaigning against devolution to sitting in the Scottish Parliament and Welsh Assembly.